A study on the effect of varying pressure and distance on material hardening in INTI Plasma Focus Machine - Arwinder, Singh; Teh, Thiam Oun; Goh, Eng Hoe; Saw, Sor Heoh; Lee, Sing (INTI International University, 2020)
Material hardening is a topic of much interest. In this paper, material hardening on AISI 1020 low carbon steel was done using INTI plasma focus (INTI PF) machine. It was found that the best distance for optimum hardening was to place the sample material 4 cm from the anode at a pressure of 1 Torr when the plasma machine is operating at 12 kV as it improves the hardening by 97.8%. Computation with the Lee codes produce plots of ion beam energy versus pressure and number of ions versus pressure. Thus we are able to correlate the optimum hardness of the treated sample surface to the interaction of optimum beam energy and number of ions.